Lowered cutoff points of obesity indicators are better predictors of hypertension and diabetes mellitus in premenopausal Taiwanese women. Issue 4 (July 2015) - Chu, Fu-Ling; Hsu, Chung-Huei; Jeng, Chii
Summary: Introduction: In previous study, we found that in order to prevent MS in women aged <65 years, the cutoff points of obesity indicators should be lowered. Objective: To investigate whether our proposed cutoff points of obesity indicators predict the occurrence of hypertension (HT), diabetes mellitus (DM), and hyperlipidemia in premenopausal women with greater sensitivity and specificity compared to reference cutoff points of obesity that are currently being used. Methods: Using the database of the "2002 Survey on the Prevalence of Hypertension, Hyperglycemia and Hyperlipidemia in Taiwan" provided by the Bureau of Health Promotion, Taiwan as research material, data from 2270 premenopausal women aged 20–65 years were used for the analyses. The receiver-operating characteristic curves (ROC) of the body-mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR) were used to predict HT, DM, and hyperlipidemia. Results: Obesity is not a good predictor of the occurrence of hyperlipidemia in premenopausal women aged <65 years. However, our proposed cutoff points had greater sensitivity and specificity than did the reference cutoff points. To prevent the risk of HT and DM in premenopausal women, the cutoff points of obesity indicators should be reduced. The proposed values are as follows: a WHR of 0.79; a WC of 74.7 cm; a WHtR of 0.49; and a BMI of 22.3 kg/m 2 .